2020
DOI: 10.3390/life10090191
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tobacco Smoking and Smoking Cessation on Urinal miRNAs in a Pilot Study

Abstract: The diseases associated with tobacco smoking affect miRNAs and small single-stranded non-coding RNAs. However, there are no data on urinal miRNAs in healthy smokers. We searched for the possible effect of smoking and smoking cessation on miRNA urine expression. For screening, Affymetrix miRNA 4.0 arrays were used in 33 urine samples obtained from six never smokers and from current smokers in three time-points before smoking cessation (n = 10), after short time abstinence (3–8 weeks), and after long-term abstin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Tobacco-rich compounds such as aromatic amines and N-nitroso can induce DNA damage in the form of double-strand breaks, base modifications, or bulky adduct formation (Stern et al 2009 ). Recent studies have suggested the possibility of tobacco smoking-induced oncogenic or antioncogenic gene expression by miRNA regulation in BCa (Cumberbatch et al 2018 ; Navratilova et al 2020 ). Hence, the analysis of the effect of recurrent genetic aberration in smoking and non-smoking groups of patients is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco-rich compounds such as aromatic amines and N-nitroso can induce DNA damage in the form of double-strand breaks, base modifications, or bulky adduct formation (Stern et al 2009 ). Recent studies have suggested the possibility of tobacco smoking-induced oncogenic or antioncogenic gene expression by miRNA regulation in BCa (Cumberbatch et al 2018 ; Navratilova et al 2020 ). Hence, the analysis of the effect of recurrent genetic aberration in smoking and non-smoking groups of patients is essential.…”
Section: Discussionmentioning
confidence: 99%